2012
DOI: 10.1016/j.tra.2012.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Do parking requirements significantly increase the area dedicated to parking? A test of the effect of parking requirements values in Los Angeles County

Abstract: Minimum parking requirements are the norm for urban and suburban development in the United States (Davidson and Dolnick (2002)). The justification for parking space requirements is that overflow parking will occupy nearby street or off-street parking. and Willson (1995) provides cases where there is reason to believe that parking space requirements have forced parcel developers to place more parking than they would in the absence of parking requirements. If the effect of parking minimums is to significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 28 publications
1
29
1
Order By: Relevance
“…In practice, MPRs cause an oversupply of parking spaces, lower the density of commercial and residential development, and increase housing costs. Cutter and Franco (2011) found that MPRs distorted land use decisions by forcing developers in Los Angeles to provide more parking than they otherwise would; McDonnell, Madar, and Been (2011) reached a similar conclusion about the effect of MPRs in the New York metropolitan area. Manville (2010) evaluated a 1999 experiment in Los Angeles that exempted vacant commercial and industrial buildings from MPRs if they were converted into housing and found that developers provided more housing and less parking than they would have provided if MPRs were in place.…”
Section: Congestionmentioning
confidence: 92%
“…In practice, MPRs cause an oversupply of parking spaces, lower the density of commercial and residential development, and increase housing costs. Cutter and Franco (2011) found that MPRs distorted land use decisions by forcing developers in Los Angeles to provide more parking than they otherwise would; McDonnell, Madar, and Been (2011) reached a similar conclusion about the effect of MPRs in the New York metropolitan area. Manville (2010) evaluated a 1999 experiment in Los Angeles that exempted vacant commercial and industrial buildings from MPRs if they were converted into housing and found that developers provided more housing and less parking than they would have provided if MPRs were in place.…”
Section: Congestionmentioning
confidence: 92%
“…Arnott and Rowse (2009) model this spatial competition, taking into account the technology of garage construction. But, here, we provide a simpler treatment, 12 in order to simplify analysis.…”
Section: Downtown Tra¢ C Congestion With Both Curbside and Garage Parmentioning
confidence: 99%
“…We come back to this in the conclusion. Cutter and Franco, 2012). Nevertheless, they can be found in San Francisco, Chicago and Boston and have recently been approved in New York.…”
mentioning
confidence: 99%